Solidarity with solidarity : Western European trade unions and the Polish crisis, 1980-1982 - Goddeeris, Idesbald, 1972- (Harvard Cold War studies book series., 2010)
The Polish crisis in the early 1980s provoked a great deal of reaction in the West. Not only governments, but social movements were also touched by the changes. This book analyzes Western European social reaction to the Independent Self-governing Trade Union Solidarnosc, Revealing how many unionists hesitated between dZtente and workers' rights, between Atlantic cold warriors and European cooperation. It provides new insights relevant to historians dealing with the Cold War, Labor, and European integration.